Seroprevalence of Neutralizing Antibodies to Human Adenovirus Type 4 and 7 in Healthy Populations From Southern China - Ye, Xianmiao; Xiao, Lijun; Zheng, Xuehua; Wang, Jinlin; Shu, Tao; Feng, Ying; Liu, Xinglong; Su, Wan; Wang, Qian; Li, Chufang; Chen, Ling; Feng, Liqiang (Frontiers in Microbiology, 2018)
Human adenoviruses type 4 (HAdV4) and 7 (HAdV7) are two major respiratory pathogens and sporadically cause outbreaks of acute respiratory diseases. The neutralizing antibody (nAb) response to these two adenoviruses in civilian populations, which is important for dissecting previous circulations and predicting potential outbreaks, remains largely unknown. In this study, we generated replication-competent HAdV4 and HAdV7 reporter viruses expressing secreted-alkaline-phosphatase (SEAP), and established neutralization assays to investigate the seroprevalence of pre-existing nAb in healthy volunteers from Hunan Province, southern China. The seropositivity rates are 58.4% and 63.8% for anti-HAdV4 nAb and anti-HAdV7 nAb, respectively. High nAb titers (>1000) were frequently detected in HAdV4-seropositive individuals, whereas most HAdV7-seropositive volunteers had moderate nAb titers (201-1000). The seropositivity rates of anti-HAdV4 nAb and anti-HAdV7 nAb increase with age, with individuals younger than 20 exhibiting the lowest seropositivity rates. Both seropositivity rates and nAb titers are comparable between different sex groups. Notably, HAdV4-seropositive individuals tend to be HAdV7-seropositive and vice versa. Because HAdV4 antisera showed no neutralizing activity to HAdV7 whereas HAdV7 antisera cannot neutralize HAdV4, a subgroup of individuals might be susceptible to infection by HAdV4 and HAdV7 and thus generate nAb to both of them. These results revealed the continuous circulation of HAdV4 and HAdV7 and the lack of protective immunity in more than 35% of people, which emphasized the surveillance of these two HAdVs and the development of prophylactic vaccines.